The politics of salvation Lukan soteriology, atonement, and the victory of Christ - Reardon, Timothy W. (London T&T Clark, 2020)
Preface Acknowledgements Abbreviations -- 1. Defining Spaces: Religion, Politics, and Luke-Acts -- 2. An Inbreaking Salvation (Luke 1:68-79) -- 3. Jesus, Herald of God's Kingdom (Luke 4:18-19) -- 4. Heaven Invading: The Holy Spirit, Church, and Salvific Space (Acts 1-2) -- 5. The Mission of Salvation and Historical Recurrence (Acts 13:16-52) Conclusion Bibliography
"Timothy W. Reardon uncovers the Lukan salvation narrative developed within Acts, and its key themes that include its presentation of time and space, while also being attentive to overcoming a facile compartmentalization of religion and politics"--
Includes bibliographical references and index
Also published in print.
Reproduktion
Mode of access: World Wide Web.
Barrierefreier Inhalt: Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc; Salvation -- Christianity -- Biblical teaching; Biblical studies & exegesis; Electronic books